Employment stickiness in small manufacturing firms - Philip Vermeulen (European Central Bank (ECB), 2006)
Small firms often do not change their number of employees from year to year. This paper investigates the role of adjustment costs and indivisibility of labor in the employment stickiness of manufacturing firms with less than 75 employees. When small firms have to adjust employment in units of at least one employee, indivisibility becomes an important source of stickiness. A structural model of dynamic labor demand with adjustment costs and indivisibility is estimated using indirect inference on a panel of small French manufacturing firms. Adjustment cost are estimated to be very small. Indivisibility explains around 50% of the stickiness of employment, adjustment costs explain the other 50%.
Keywords: E24; 330; Employment; indirect inference; indivisibility; labor adjustment costs; sticky employment; KMU; Kündigung; Personalplanung; Arbeitsnachfrage; Theorie; Frankreich